2015
DOI: 10.1155/2015/794109
|View full text |Cite
|
Sign up to set email alerts
|

Role of GeneXpert MTB/Rif Assay in Diagnosing Tuberculosis in Pregnancy and Puerperium

Abstract: Presentation of tuberculosis (TB) in pregnancy may be atypical with diagnostic challenges. Two patients with complicated pregnancy outcomes, foetal loss and live premature delivery at 5 and 7 months of gestation, respectively, and maternal loss, were diagnosed with pulmonary TB. Chest radiography and computed tomography showed widespread reticuloalveolar infiltrates and consolidation with cavitations, respectively. Both patients were Human Immunodeficiency Virus (HIV) seronegative and sputum smear negative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…[7][8][9][10]14,15] TB is also the leading cause of non-obstetricrelated maternal death. [16][17][18] There are various reasons for the lack of maternal TB screening recommendations and implementation in low-resource, TBendemic countries.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10]14,15] TB is also the leading cause of non-obstetricrelated maternal death. [16][17][18] There are various reasons for the lack of maternal TB screening recommendations and implementation in low-resource, TBendemic countries.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, Balcha et al 24 e Weyer et al 40 sugeriram que o GeneXpert seja utilizado de forma adjunta à baciloscopia. Habib et al 41 relataram que, em pacientes grávidas, o GeneXpert obteve melhor sensibilidade, detectando a doença com maior rapidez, com destaque para os casos com baciloscopia negativa.…”
Section: Discussionunclassified
“…19 The number of studies using Xpert ® to diagnose TB in pregnancy are limited: a cross-sectional study among 306 HIV-positive Kenyan pregnant women seeking ANC in Western Kenya reported a lower sensitivity of 43%, 32 while a study among obstetric and gynaecologic inpatients had a sensitivity of 80.8% 17 and a case report, which recommended Xpert ® as point-of-care screening tool, described two HIV-and acid-fast bacilli-negative pregnant women diagnosed with TB using Xpert ® . 33 Botswana's TB diagnostic algorithm currently includes Xpert ® as the initial TB diagnostic test for all presumed TB cases, including pregnant women. 10 However, this does not address the TB screening and early diagnostic challenge among pregnant women having low sensitivity (28%) for symptomatic TB screening.…”
Section: Public Health Actionmentioning
confidence: 99%